The Influence Of Work-Life Balance And Emotional Intelligence On Organizational Commitment Of Perumda Tirta Pakuan Employees, Bogor City - Selina Aryadisti; Sri Harini; Ismartaya (Fakultas Ekonomi Universitas Djuanda, 2024)
The purpose of this study was to determine the influence and employee responses regarding work-life balance and emotional intelligence on organizational commitment. This research method is quantitative research with proportionate random sampling technique. Data collection through distributing questionnaires tested through validity, reliability, multicollinearity, heteroscedasticity, regression coefficient, coefficient of determination, F test, and t test. The results of the study are work-life balance, emotional intelligence, and organizational commitment of employees in the high enough category. In addition, work-life balance and emotional intelligence have a positive and significant effect on employee organizational commitment both simultaneously and partially. ABSTRAK Tujuan penelitian ini ialah untuk mengetahui pengaruh dan tanggapan pegawai mengenai work-life balance dan kecerdasan emosional terhadap komitmen organisasional. Metode penelitian ini ialah penelitian kuantitatif dengan teknik proportionate random sampling. Pengumpulan data melalui penyebaran kuesioner yang diuji melalui uji validitas, reliabilitas, multikolineriatas, heterokedastisitas, koefisien regresi, koefisien determinasi, uji F, dan uji t. Hasil penelitian yakni work-life balance, kecerdasan emosional, dan komitmen organisasional karyawan berada pada kategori cukup tinggi. Selain itu, work-life balance dan kecerdasan emosional berpengaruh positif dan signifikan terhadap komitmen organisasional karyawan baik secara simultan maupun parsial.